Food and jewish identity in Margo Glantz' Las genealogias - Balutet, Nicolas (Romanica Olomucensia, 2014)
Since the 70s and the necessary emergence of feminist movements in the public sphere, we often think that food is a form of subjugation of women. At first glance, this is the idea that emerges from Las genealogias (1981), autobiography by Mexican writer Margo Glantz (1930-) that tells the story of Jewish immigrants from Ukraine. In its effort to decipher its Judeo-Mexican identity, the author relies almost exclusively on his father and his literary activities while his mother is relegated to the kitchen. This article seeks to demonstrate, however, that the text does not discredit Lucia Glantz. The food facilitates the emergence of memories and strengthens the links between past and present. If Las genealogias more highlights the figure of the father, this work seems to indicate that food, as well as books, helps to the acquisition of knowledge, which is not surprising if we remember that knowledge and taste have the same etymology.
Keywords: identity; Judaism; food; memory; Mexico.